Risk management - Ramakrishna Reddy, K.; Murali Krishna, P. (New Delhi : Discovery Pub. House, 2000)
In the Indian context; contributed articles.
Keywords: Agricultural insurance; Insurance -- Management; Risk management; Agriculture -- Economic aspects